Studying the effect of remapping on the 21 cm map mocks. Issue 1 (11th December 2022) - Mokeddem, Rahima; Hipolito‐Ricaldi, W. S.; Zhang, Jiajun
Abstract: In cosmology, the construction of simulated mocks is very important to mimic real observations before they are available. Mocks allow, for example, to test the data analysis pipeline or to perform some forecast in an observational project. In this work, we present very preliminary results in constructing the 21 cm mocks by extending the remapping of dark matter halo catalogs. The remapping process helps to start from a given N‐body simulation catalog to construct a new N‐body catalog in another cosmology without the necessity of running an N‐body simulation each time. This allows us to get different N‐body statistics faster and in a computationally more efficient way.